2016
DOI: 10.1039/c6an00752j
|View full text |Cite
|
Sign up to set email alerts
|

Employment of electrostatic interactions for amperometric detection of carbon nanoparticles in a FIA system

Abstract: The development of methods for nanoparticle detection is highly desirable due to their increasing presence in the environment. Recently, we have shown that the electrochemical detection in flow is one of the possible solutions. Here we demonstrate a dramatic improvement of analytical parameters of such detection. The significant enhancement of an amperometric signal resulting from the electrocatalytic oxidation of ascorbic acid (AA) in a negatively charged phenylsulphonated carbon nanoparticle suspension in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Recently, we and others demonstrated that it is possible to record the amperometric response of the catalytic nanoparticles from the background current on standard size disc electrodes (diameter in the range of millimetres) in forced convection conditions. This was done in both flow system and with rotating disc electrode . It was concluded, that adsorption of catalytic nanoparticles provides suitable conditions for discrimination of the faradaic from capacitive current.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Recently, we and others demonstrated that it is possible to record the amperometric response of the catalytic nanoparticles from the background current on standard size disc electrodes (diameter in the range of millimetres) in forced convection conditions. This was done in both flow system and with rotating disc electrode . It was concluded, that adsorption of catalytic nanoparticles provides suitable conditions for discrimination of the faradaic from capacitive current.…”
Section: Introductionmentioning
confidence: 77%
“…It occurs when CNPs + are in direct contact with the ITO surface, long enough to allow for multiple electron transfer . CNPs + catalyze AA oxidation in the absence of any other catalytic component similarly like CNPs − deliberately deposited on the electrode surface or adsorbed from suspensions . However, the change of functional groups from negatively to positively charged results in an increase of current density.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependence of peak current on AuNPs concentration is power‐law (Figure ). The high sensitivity is presumably a consequence of strong interactions between positively charged NPs and polyvalent sulphite anions , . As a result, i) the AuNPs are attracting substrate, then ii) the effective charge of gold nanoparticles’ surface is reversed and the surrounded AuNPs are stronger attracted to a positively charged working electrode (+1.2 V).…”
Section: Resultsmentioning
confidence: 99%
“…The response and reproducibility on a single ITO electrode (blue points in Figure ) is similar to those with the disposable ITO electrodes (red points in Figure ). This suggests that a memory‐effect of electrode does not appear at all , and AuNPs desorb from the electrode surface. Moreover, the shape of the current‐time dependence (Figure ) indicates a lack of sensitivity loss in time.…”
Section: Resultsmentioning
confidence: 99%